2011
DOI: 10.1016/j.conb.2011.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception and saccadic eye movements

Abstract: We use saccades several times per second to move the fovea between points of interest and build an understanding of our visual environment. Recent behavioral experiments show evidence for the integration of pre- and postsaccadic information (even subliminally), the modulation of visual sensitivity, and the rapid reallocation of attention. The recent physiological literature has identified a characteristic modulation of neural responsiveness - perisaccadic reduction followed by a postsaccadic increase that is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
120
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(147 citation statements)
references
References 64 publications
20
120
1
Order By: Relevance
“…Interactions between image-aligned and fixation-aligned activity Saccadic suppression has been described behaviorally (Latour, 1962;Burr et al, 1994), and at the neural level (Thiele et al, 2002;Bremmer et al, 2009), but few studies have focused on its corollary: the enhancement of visual processing following a saccade (for review, see Ibbotson and Krekelberg, 2011). We demonstrated that visual inputs and fixation-locked activity in uSTS show a supra-additive interaction.…”
Section: Fixation-aligned Residual Activitymentioning
confidence: 76%
See 1 more Smart Citation
“…Interactions between image-aligned and fixation-aligned activity Saccadic suppression has been described behaviorally (Latour, 1962;Burr et al, 1994), and at the neural level (Thiele et al, 2002;Bremmer et al, 2009), but few studies have focused on its corollary: the enhancement of visual processing following a saccade (for review, see Ibbotson and Krekelberg, 2011). We demonstrated that visual inputs and fixation-locked activity in uSTS show a supra-additive interaction.…”
Section: Fixation-aligned Residual Activitymentioning
confidence: 76%
“…For example, in primary visual cortex, fixation onset in darkness leads to a resetting of oscillations to a phase associated with high firing rates (Rajkai et al, 2008), and during visual stimulation, fixation onset leads to increased firing rates (Gallant et al, 1998;MacEvoy et al, 2008), spike synchronization (Maldonado et al, 2008;Ito et al, 2011), and sparseness (Vinje and Gallant, 2000). Whereas both saccadic suppression and enhancement following fixation are seen in many visual areas (for review, see Ibbotson and Krekelberg, 2011), they are poorly understood in object-selective visual areas. For example, it remains unclear whether visual and visuomotor signals interact to facilitate object processing in the temporal lobe.…”
Section: Introductionmentioning
confidence: 99%
“…Animals that possess retinal specializations for high visual acuity, such as primates, can improve perceptual performance on visual tasks either by overt orienting (directing the fovea toward a target stimulus) or by covert orienting (covertly monitoring the target stimulus without moving the head or eyes). For these species, orienting the optical axis of the eye to bring a stimulus on to the fovea can have an enormous impact on perceptual performance (28). However, chickens do not have foveas.…”
Section: Resultsmentioning
confidence: 99%
“…Using a different task, Young and Hollands (2012) also showed that older adults are significantly delayed in initiating gaze and steps to a target that jumps during the swing phase, a protocol that requires online corrections of foot placement. In a DS paradigm such as the one adopted in this study, the secondary eye-movement to the second target displacement requires the computation of a retinal error signal resulting from the extinction of the first light and the illumination of the second, as well as a prediction of the position of the second light target to finely tune final eye position (Duhamel et al 1992;Gredeback and Kochukhova 2010;Ibbotson and Krekelberg 2011;Wong and Shelhamer 2012). Our linear regressions (Fig.…”
Section: Figure 6 About Herementioning
confidence: 99%